Desemprego e relaç\~oes familiares em regi\~oes metropolitanas: Condiç\~oes de vida e estratégias de acesso a recursos - Vitor Matheus Oliveira de Menezes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article investigates the socioeconomic impacts of unemployment on different groups of individuals, and specially addresses the family circulation of goods and services during the job search. For this, it examines the vocabularies of 245 workers in semi-structured interviews carried out by the Institute for Applied Economic Research (Ipea) from 2015 to 2016, within the scope of the Radiography of Contemporary Brazil project. The data were submitted to a statistical technic called Hierarchical Descending Cluster Analysis, producing four lexical classes. After, a factorial correspondence analysis inserted the lexicons in a cartesian plan, showing two splits, one thematic and another by the number of available resources. The results contrast the experiences of poor workers, for whom the unemployment is bounded to the dispute for basic needs, with the experiences of groups with guaranteed access to resources, whose family repertories are directed to the search for better jobs. The analysis distinguishes, besides, a precarious job insertion and another that occurs in more stable trajectories. Finally, chi-squared tests associated these lexical classes with sex, race, and schooling indicators.
Keywords: D10; J12; J13; M52; 330; unemployment; family; labor market; inequality; lexical analysis